2014
DOI: 10.1002/jcu.22126
|View full text |Cite
|
Sign up to set email alerts
|

Decreased aorto‐septal angle may contribute to left ventricular diastolic dysfunction in healthy subjects

Abstract: Background: Left ventricular (LV) diastolic dysfunction is often observed in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(76 reference statements)
2
8
0
Order By: Relevance
“…A change in LV shape associated with a decrease in the ASA has been observed in healthy older subjects, which we confirmed in our study . Some have argued that this finding is related to diastolic dysfunction; in a study of 77 subjects (mean age 43 ± 14 years, 42 men), Okada and co‐workers showed that ASA significantly correlated with E ( r = 0.54, P < 0.001), isovolumic relaxation time (IRT) ( r = −0.41, P < 0.001), e′ ( r = 0.57, P < 0.01), and peak early‐diastolic myocardial global strain rate ( r = 0.63, P < 0.001) and hypothesized that reduced ASA may be related to LV diastolic dysfunction . Our data support the notion that decreased ASA is part of the presbycardia phenotype, which includes diastolic dysfunction, but we do not suggest that there is necessarily a causal relationship.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A change in LV shape associated with a decrease in the ASA has been observed in healthy older subjects, which we confirmed in our study . Some have argued that this finding is related to diastolic dysfunction; in a study of 77 subjects (mean age 43 ± 14 years, 42 men), Okada and co‐workers showed that ASA significantly correlated with E ( r = 0.54, P < 0.001), isovolumic relaxation time (IRT) ( r = −0.41, P < 0.001), e′ ( r = 0.57, P < 0.01), and peak early‐diastolic myocardial global strain rate ( r = 0.63, P < 0.001) and hypothesized that reduced ASA may be related to LV diastolic dysfunction . Our data support the notion that decreased ASA is part of the presbycardia phenotype, which includes diastolic dysfunction, but we do not suggest that there is necessarily a causal relationship.…”
Section: Discussionsupporting
confidence: 89%
“…10,11 Some have argued that this finding is related to diastolic (r = −0.41, P < 0.001), e′ (r = 0.57, P < 0.01), and peak early-diastolic myocardial global strain rate (r = 0.63, P < 0.001) and hypothesized that reduced ASA may be related to LV diastolic dysfunction. 16 Our data support the notion that decreased ASA is part of the presbycardia phenotype, which includes diastolic dysfunction, but we do not suggest that there is necessarily a causal relationship.…”
Section: Septal Angulationsupporting
confidence: 53%
“…A sigmoid septum (also denoted as ventricular septal bulge or angled aorta) is considered a normal variant or a minor abnormality often encountered in echocardiographic examinations of the elderly [12][13][14][15]23]. Sometimes, distinguishing between the SS and hypertrophic cardiomyopathy can be problematic because SS can cause an LV outflow tract obstruction [24][25][26][27][28].…”
Section: Impact Of Sigmoid Septum On Rv Shapementioning
confidence: 99%
“…Sometimes, distinguishing between the SS and hypertrophic cardiomyopathy can be problematic because SS can cause an LV outflow tract obstruction [24][25][26][27][28]. It has been also reported that subjects with SS more frequently have hypertension, greater relative wall thickness, and LV diastolic dysfunction [15,23,30].…”
Section: Impact Of Sigmoid Septum On Rv Shapementioning
confidence: 99%
See 1 more Smart Citation